(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The increasing population and high cost of fuels have created opportunities for using alternate energies for the processing of foods. Solar processing is an emerging sustainable energy technology that provides good quality foods at low or no additional fuel costs. The present investigation is an attempt to design and explore solar driers for traditional and ethnic food i.e Churpi cheese and Bandel cheese. They are found in Nepal and Eastern- India, Bandel, and West Bengal respectively. The objective was to modify these two traditional kinds of cheese and produced a nutritive, value-added, ready-to-eat cheese by applying a solar drying process. Drying was accomplished in an indigenously designed solar dryer maintained at around 700C, to reduce 77% moisture content. Solar drying technology was used, as it is cost-effective and minimizes micro and macronutrient losses during the drying process. The physical properties and proximate composition of ready-to-eat cheese were analyzed. The sensory panel of this cheese rated more acceptable.